Confinement of Iodine Molecules into Triple-Helical Chains within Robust Metal–Organic Frameworks - Zhang, Xinran (J Am Chem Soc, 2017)
[Image: see text] During nuclear waste disposal process, radioactive iodine as a fission product can be released. The widespread implementation of sustainable nuclear energy thus requires the development of efficient iodine stores that have simultaneously high capacity, stability and more importantly, storage density (and hence minimized system volume). Here, we report high I(2) adsorption in a series of robust porous metal–organic materials, MFM-300(M) (M = Al, Sc, Fe, In). MFM-300(Sc) exhibits fully reversible I(2) uptake of 1.54 g g(–1), and its structure remains completely unperturbed upon inclusion/removal of I(2). Direct observation and quantification of the adsorption, binding domains and dynamics of guest I(2) molecules within these hosts have been achieved using XPS, TGA-MS, high resolution synchrotron X-ray diffraction, pair distribution function analysis, Raman, terahertz and neutron spectroscopy, coupled with density functional theory modeling. These complementary techniques reveal a comprehensive understanding of the host–I(2) and I(2)–I(2) binding interactions at a molecular level. The initial binding site of I(2) in MFM-300(Sc), I(2)(I), is located near the bridging hydroxyl group of the [ScO(4)(OH)(2)] moiety [I(2)(I)···H–O = 2.263(9) Å] with an occupancy of 0.268. I(2)(II) is located interstitially between two phenyl rings of neighboring ligand molecules [I(2)(II)···phenyl ring = 3.378(9) and 4.228(5) Å]. I(2)(II) is 4.565(2) Å from the hydroxyl group with an occupancy of 0.208. Significantly, at high I(2) loading an unprecedented self-aggregation of I(2) molecules into triple-helical chains within the confined nanovoids has been observed at crystallographic resolution, leading to a highly efficient packing of I(2) molecules with an exceptional I(2) storage density of 3.08 g cm(–3) in MFM-300(Sc).